Structure of Tree Community on Agroforestry Parak in Peri-Urban Areas District of Lubuk Alung Padang Pariaman - Reki Kardiman; Irma Leilani (UNIVERSITAS NEGERI PADANG, 2023)
Agroforestry or tree crops in West Sumatra is called parak, it mostly related to rural and farmers but at some developing areas the parak is still existed with a high potential changes in structure and floristic composition due to commercial orientation. To explore the possible changes of tree community in such developing areas, 11 of 20x20 meter plots were established across parak areas in peri-urban site in Lubuk Alung district, Padang Pariaman Regency, West Sumatra Indonesia, aimed to specifically investigate tree density, stand basal area, spesies distribution and other ecological atributes of the species. We found 24 tree species from 306 trees within 0.44 ha or about 695 tree per ha. Durio zibethinus was the biggest trees, found as a top canopy but few in number and spreaded quite widely across the areas, followed by some other species such as Cocos spp., Areca catecu, Garcinia spp., while small trees, high density but only spreaded at some places was represented by Theobroma cacao. Many species and the structure were typically agroforest that vary in canopy level and economic functions except some species which may be additionally planted to suit the needs of peri-urban community.